Real-time spherical near-field handset antenna measurements. - Iversen, P.O.; Garreau, Ph.; Burrell, Dennis
A new spherical near-field measurement system, dedicated to personal-communications applications, has been installed at e-tenna Corporation. The system, sold by Satimo, uses an electronically scanned probe array, and offers a dramatic reduction of the measurement time (by a factor ranging from 60 to 1,000) with respect to conventional mechanical scanners. This test range has undergone extensive acceptance testing, which has verified the specified measurement accuracy. The speed of the system, combined with the availability of full-sphere measurement data, enables rapid measurement of antenna efficiency. The system also enables the measurement of other parameters, such as the percentage of radiated power dissipated into the body of a human test subject operating a cellular telephone.
Keywords: Electric field measurement; Antenna radiation patterns; Compact range measurements; Telephone sets; Land mobile radio cellular systems; Spherical near field measurements; Near field measurements